Hubungan Variasi Durasi Lama Puasa Dengan Status Hemodinamik Dan Kadar Gula Darah Pada Pasien Bedah Elektif - Irwadi, Irwadi; Heri Wibow, Tophan; Lintang Suryani, Roro; Budi, Martyarini (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Preoperative fasting is important before differentiation to prevent aspiration. The American Society of Anesthesiologists (ASA) guidelines recommend a minimum of 6 hours of fasting, but in practice, longer fasting durations negatively impact the patient's hemodynamic and metabolic status. This study aims to analyze the relationship between variations in fasting duration and hemodynamic status, as well as blood sugar levels, in elective surgical patients. This study used a quantitative cross-sectional approach design with a sample of 135 elective surgical patients collected by purposive sampling. Spearman Rank test analysis showed a significant negative relationship between variations in fasting duration and blood sugar levels (r = -0.380; p = 0.001). No significant relationship was found between variations in fasting duration and diastolic blood pressure, diastolic, MAP, pulse rate, and oxygen saturation (p > 0.05). In conclusion, variations in fasting duration are associated with blood sugar levels, but do not affect hemodynamics. These findings underscore the importance of preoperative fasting duration management to maintain metabolic and physiological stability in elective surgery patients.